Peroxyacetyl nitrate measurements by thermal dissociation-chemical ionization mass spectrometry in an urban environment： performance and characterizations - Wang, Xinfeng; Wang, Tao; Xue, Likun; Nie, Wei; Xu, Zheng; Poon, Steven C. N.; Wang, Wenxing (Frontiers of environmental science & engineering, 2017)
Peroxyacetyl nitrate （PAN） is an important indicator of photochemical smog and has adverse effects on human health and vegetation growth. A rapid and h!ghly selective technique of thermal dissociation chemical ionization mass spectrometry （TD-CIMS） was recently developed to measure the abundance of PAN in real time; however, it may be subject to artifact in the presence of nitric oxide （NO）. In this study, we tested the interference of the PAN signal induced by NO, evaluated the performance of TD- CIMS in an urban environment, and investigated the concentration and formation of PAN in urban Hong Kong. NO caused a significant underestimation of the PAN signal in TD-CIMS, with the underestimation increasing sharply with NO concentration and decreasing slightly with PAN abundance. A formula was derived to link the loss of PAN signal with the concentrations of NO and PAN, which can be used for data correction in PAN measurements. The corrected PAN data from TD- CIMS were consistent with those from the commonly used gas chromatography with electron capture detection, which confirms the utility of TD-CIMS in an urban environment in which NO is abundant. In autumn of 2010, the hourly average PAN mixing ratio varied from 0.06 ppbv to 5.17 ppbv, indicating the occurrence of photochemical pollution in urban Hong Kong. The tbrmation efficiency of PAN during pollution episodes was as high as 3.9 to 5.9 ppbv per 100 ppbv ozone. The efficiency showed a near-linear increase with NO, concentration, suggesting a control policy of NO,. reduction for PAN pollution.